KETIDAKSINKRONAN HUKUM MENGHAMBAT INVESTASI - Made Warka (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2007)
Dyssynchronization of law in investment Held happens in vertical and horizontal relationship. For example, relationship between the Decree of Investment Ministry/ Chief of Capital Investment Coordinator Agency Number 37/SK/1999, it follows decentralization principle. When it is related with the Decree of President of Republic of Indonesia Number 29 Year 2004, it follows centralization principle. According to Law Number 32 Year 2004, in the relationship between Regency/City government with another there is dyssynchronization because each regions only sued for optimal PAD increment, therefore many regional rules (Perda) which are established by Regency/City government tend to obstruct capital investment in the Regency/City area. With dyssynchronization above, there is uncertainty concerning with the effect of law to investor, and finally, the number of unemployment is increasing.